KEBERHASILAN PENEMPATAN KERJA BERDASARKAN PADA KECERDASAN INTELEKTUAL (IQ) DAN MOTIVASI DIRI DI POLITEKNIK LP3I JAKARTA - Rahayu Tri Utami; rahmi rosita (POLITEKNIK LP3I JAKARTA, 2019)
Placement is a very decisive process in getting employees in accordance with what is needed by the company, because the right placement of employees in a position will be able to assist the company in achieving the expected goals. The method used in this method is an evaluation research method which means